Bidirectional Relationship Between Nanoarteritic Ischemic Optic Neuropathy with Diabetes Mellitis: A Cross Sectional Study - Sadia Islam, Asma Kazi, Aisha Aziz, Tashfeen Ikram, Zia Ul Mustafa, Muhammad Aleem Uddin, Mufassar Nishat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes, low nighttime blood pressure, and nonarteritic ischemic optic neuropathy may be associated. Not too many studies present whether this relationship applies to patients. Objective: Diabetes mellitus, low blood pressure at night, and nonarteritic ischemic optic neuropathy were studied in a group of individuals. Methods: The ophthalmology clinic will conduct a cross-sectional research on patients with nonarteritic ischemic optic neuropathy from March 2019 to December 2021. Nonarteritic ischemic optic neuropathy patients were tested for diabetes. Some participants wore ambulatory blood pressure monitors during the trial. Nighttime blood pressure drops are typical, muted, severe, and reverse. Results: Nonarteritic ischemic optic neuropathy was identified in 67 individuals. 587 of 67 patients were selected. 34 patients (50.7%) had diabetes, while 39 (58.2%) had hypertension. 32 people’s blood pressure dropped during sleep. Only four (5.9%) saw substantial drops. Conclusions: Diabetes may be linked to nonarteritic ischemic optic neuropathy, but not nocturnal blood pressure declines. Keywords: Optic Neuropathy, Diabetes Mellitus, Hypertension